ANALISIS FINANSIAL TANAMAN KARET (Hevea brasiliensis) AREAL PT. INHUTANI III KERJASAMA OPERASI (KSO) DENGAN PT. CITRA PUTRA KEBUN ASRI KABUPATEN TANAH LAUT - Elok Koeswindarti; Arfa Agustina Rezekiah; Muhammad Helmi (Jurnal Sylva Scienteae, 2021)
This study aims to analyze the financial feasibility of PT. Citra Putra Kebun Asri in the area of PT. Inhutani III Tanah Laut Regency. This research method uses financial analysis methods including NPV, Net B / C and IRR. The results of this study indicate the financial feasibility analysis obtained using a discount rate of 9.95% with the NPV method of Rp11,384,378,028, - net B / C value of Rp1,202 and IRR of 12,702%. PT. Citra Putra Kebun Asri (CPKA) in developing the rubber plant business is very beneficial for the company itself so that the estate is financially feasible to continue.Keywords: Financial analysis; NPV; Net B/C; IRR